COMPARISON OF STUDENTS’ SCIENTIFIC LITERACY IN INTEGRATED SCIENCE LEARNING THROUGH MODEL OF GUIDED DISCOVERY AND PROBLEM BASED LEARNING (Jurnal Pendidikan IPA Indonesia, 2016)
This study aims to describe the comparison of students’ scientific literacy improvement in integrated science learning through guided dicovery and problem based learning models. The subjects were 8th grade students of State Junior High Schools in Bandung. This research design was quasi-experimental with non randomaized static group pretest-posttest design. The instrument used in this study was multiple choice test and attitude scale. The result shows that the improvement of scientific literacy achievement of students who learned integrated science through guided discovery and problem based learning models did not differ significantly. Integrated science learning through guided disovery models can improve student literacy achievement with the gain of 0.37 (medium category), while by using problem based learning model can improve scientific literacy with the gain of 0.41 (medium category). It can be concluded that the both models of guided discovery and problem based learning can improve students' science literacy.